Magma ascent rates in explosive eruptions: Constraints from H2O diffusion in melt inclusions - Humphreys, M; Menand, T; Blundy, J; Klimm, K (2008)
The pre-fragmentation velocity of magma ascending during explosive volcanic eruptions remains difficult to quantify. Here we present a new technique for using syn-eruptive volatile diffusion in imperfectly trapped melt inclusions to obtain a direct estimate of such ascent velocities. H 2O diffusion profiles are obtained from back-scattered electron images of synthetic, partially hydrated glasses and tube-shaped melt inclusions. The greyscale intensity of glass in the images shows a good negative linear correlation with melt H 2O concentration. Greyscale intensity profiles, extracted using image-processing software, can therefore be calibrated against H 2O measured at discrete points by ion microprobe. An advantage of the technique is that concentration profiles can be determined in melt tubes that are too small to analyse directly, with a spatial resolution (≤ 1 μm) that is considerably better than that obtainable by ion microprobe or FTIR. A finite element model, which incorporates previously published estimates of concentration-dependent H 2O diffusivity, is used to fit the resulting continuous concentration profiles. We apply the technique to tube-shaped melt inclusions from the May 18th, 1980 Plinian eruption of Mount St Helens, Washington, USA. The model produces good fits to the data, indicating very rapid ascent times of between 102 and 166 s, which correspond to mean ascent velocities of 37-64 m/s, or mean decompression rates of 0.9-1.6 MPa/s. These are in agreement with previous estimates from petrological studies and numerical modelling. © 2008 Elsevier B.V. All rights reserved.